Stimuli-responsive hybrid nanocarriers developed by controllable integration of hyperbranched PEI with mesoporous silica nanoparticles for sustained intracellular siRNA delivery - Prabhakar N (Dove Medical Press, 2016)
Neeraj Prabhakar,1,2 Jixi Zhang,3 Diti Desai,1 Eudald Casals,1 Tina Gulin-Sarfraz,1 Tuomas Näreoja,2,4 Jukka Westermarck,5,6 Jessica M Rosenholm1 1Pharmaceutical Sciences Laboratory, Faculty of Science and Engineering, Åbo Akademi University, 2Laboratory of Biophysics, Faculty of Medicine, University of Turku, Turku, Finland; 3College of Bioengineering, Chongqing University, Chongqing, People’s Republic of China; 4Department of Neuroscience, Karolinska Institute, Stockholm, Sweden; 5Centre for Biotechnology, University of Turku and Åbo Akademi, 6Department of Pathology, University of Turku, Turku, Finland Abstract: Small interfering RNA (siRNA) is a highly potent drug in gene-based therapy with the challenge being to deliver it in a sustained manner. The combination of mesoporous silica nanoparticles (MSNs) and polycations in the confined pore space allows for incorporation and controlled release of therapeutic siRNA payloads. We hereby constructed MSNs with expanded mesopores and pore-surface-hyperbranched poly(ethyleneimine) (PEI) tethered with redox-cleavable linkers that could carry a high payload of siRNA (120 mg·g-1). The developed nanocarriers were efficiently taken up by cancer cells and were subsequently able to escape to the cytoplasm from the endosomes, most likely owing to the integrated PEI. Triggered by the intracellular redox conditions, the siRNA was sustainably released inside the cells over a period of several days. Functionality of siRNAs was demonstrated by using cell-killing siRNA as cargo. Despite not being the aim of the developed system, in vitro experiments using cell-killing siRNAs showed that the efficacy of siRNA transfection was comparable to the commercial in vitro transfection agent Lipofectamine. Consequently, the developed MSN-based delivery system offers a potential approach to hybrid nanocarriers for more efficient and long-term siRNA delivery and, in a longer perspective, in vivo gene silencing for RNA interference (RNAi) therapy. Keywords: mesoporous silica nanoparticles, RNAi therapy, siRNA delivery, stimuli-responsive drug release, hybrid nanocarriers